Application of the scolding technique for managing auditory hallucinations in a patient with schizophrenia: A case study - Helena Candra Devi; Mamnuah Mamnuah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Schizophrenia is a severe mental disorder characterized by disturbances in perception, thought processes, emotions, and behaviour. Auditory hallucinations are among the most common positive symptoms experienced by individuals with schizophrenia and may interfere with daily functioning if not managed appropriately. Scolding technique are non-pharmacological nursing interventions that can help patients reduce the intensity and frequency of hallucinations by redirecting their attention to external stimuli. Purpose: To evaluate the effectiveness of the scolding technique in reducing auditory hallucinations among patients with schizophrenia. Method: A descriptive case study was conducted on one patient diagnosed with sensory perception disturbance: auditory hallucinations at Wisma Srikandi, Grhasia Mental Hospital, Yogyakarta. The nursing intervention consisted of scolding technique implemented for five consecutive days. Data were collected through observation, interviews, and nursing assessments, and outcomes were evaluated by comparing patients' signs and symptoms before and after the intervention. Results: The implementation of scolding technique reduced the frequency and severity of auditory hallucinations. Improvements were observed in the patient's ability to recognize and control hallucinations, accompanied by decreased signs and symptoms following the intervention. Conclusion: Scolding technique were effective in reducing auditory hallucinations and improving patients' ability to control hallucinatory experiences. This intervention may be considered a complementary non-pharmacological nursing strategy in the management of patients with schizophrenia experiencing auditory hallucinations. Keywords: Auditory Hallucinations; Mental Health Nursing; Schizophrenia; Scolding technique; Sensory Perception Disturbance.